2 3 —- = —- x + 2 2x – 4

Question

2 3
—- = —-
x + 2 2x – 4

in progress 0
Lệ Thu 5 months 2021-08-23T10:42:53+00:00 1 Answers 5 views 0

Answers ( )

    0
    2021-08-23T10:44:20+00:00

    Answer:

    23x-4

    Step-by-step explanation:

    x+22x-4 ( If a term doesn’t have a coefficient, it is considered that the coefficient is 1

    1x+22x-4 Collect like terms by adding their coefficients (1+22)x-4

    Then, add the numbers.

    (1+22)x-4

    23x-4

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )